The Sarawak ‘tar’ for hadrah performance - Sinin, Aaliyawani E.; Hamdan, Sinin; Mohamad Said, Khairul A.; Sawawi, Marini; Tan, Gladys Jia Jia; Hipni, Mohammad Jasni (North Carolina State University, 2024)
This work was conducted using the PicoScope signal extraction procedure, which revealed remarkable insights regarding the belian wood and its application in Sarawak traditional ‘tar’ instrument. The ‘tar’ is a small drum made of wood and attached with goat skin. A hadrah performance is done with the sound of the blow of the ‘tar’ and reciting poems praising Allah and the Prophet Muhammad by a group of players called the hadrah group. The ‘tar’ from belian wood had the highest pitch at 180 Hz i.e., F3# compared with the ‘tar’ from menggeris wood, which had the pitch D3# and A2 that also highlighted their importance in the Western scale. The overtones are not integer multiples of the fundamental frequency except for second and third overtones from ‘tar’ C (F2/F0 = 3 and F3/F0 = 4). Using Adobe Audition for Time Frequency Analysis (TFA) recordings for the ‘tar’, the data collection method provided insightful information. The communal efforts of practitioners, who are frequently grouped together, perpetuate the cultural heritage of hadrah. Essentially, by offering a thorough grasp of the intricate melodic details woven in hadrah’s cultural fabric, this research adds to the genre’s continuing heritage.